Framework and rethink of the Environmental Compensation Fund for the international seabed area - Zhou, Jiang; Xiang, Lun (Frontiers in Marine Science, 2023)
The present article addresses the system of the Environmental Compensation Fund proposed in the “Draft Regulations on Exploitation of Mineral Resources” by the International Seabed Authority (ISA). According to the documents released by the ISA, the fund aims to fill the liability gap in environmental pollution events resulting from activities in the international seabed area (the Area). Previous research has discussed the liability gap and proposed some approaches as solutions, but study of the fund is still an unexplored territory because of the absence of empirical evidence. Based on an analysis of the present regulations for the Area, this work identifies the function of the fund in covering the liability gap for environmental damage caused by the exploitation of the Area and the possible defects of this system in practice, paying particular attention to the financial regulations of ISA. The following viewpoints are put forward by this study: (1) the purpose of the fund should be limited to the scope of covering the liability gap; (2) the sources of the fund should be clarified, and sources that might increase the burden of ISA administration on the member states should be excluded; and (3) the payment procedures of the fund should be refined to meet requirements, such as speedy disbursement and full damage coverage.